Equatorial plasma bubbles features over the Brazilian sector according to the solar cycle and geomagnetic activity level - Carmo, C. S.; Dai, L.; Denardini, C. M.; Figueiredo, C. A. O. B.; Wrasse, C. M.; Resende, L. C. A.; Barros, D.; Moro, J.; Chen, S. S.; Picanço, G. A. S.; Silva, R. P.; Wang, C.; et al. (Frontiers in Astronomy and Space Sciences, 2023)
Equatorial plasma bubbles (EPBs) can lead to signal degradation affecting measurement accuracy. Studying EPBs and their characteristics has gained increasing importance. EPBs characteristics are investigated using the rate of total electron content (TEC) index (ROTI) maps in different solar and magnetic activity conditions during two periods: July 2014 to July 2015 (solar maximum activity with F10.7: 145.9 × 10−22 W⋅m−2⋅Hz−1) and July 2019 to July 2020 (solar minimum activity with F10.7: 69.7 × 10−22 W⋅m−2⋅Hz−1). We also divided this analysis according to the magnetic activity levels based on Kp and Dst (disturbance storm time) indices, classified as: quiet+ (Kp ≤ 3 and Dst > -30 nT), quiet- (Kp ≤ 3 and Dst < -30 nT), and disturbed (Kp > 3). The ROTI index is calculated using the slant TEC with the carrier-phase, and its keograms are used to extract the zonal velocity and distance. Our statistical investigation shows the occurrence rate, duration, zonal drift velocity, and inter-bubble zonal distance of EPBs over the Brazilian sector. The latitudinal extension and the zonal drift velocity of EPBs are higher during the solar maximum than in the solar minimum. In addition, EPBs are found with unusually long durations, remaining until in the morning (~12 UT), and 10% of EPBs observations occurred on the winter solstice.